Careers in graphic arts and computer graphics - McGuire-Lytle, Erin. (New York : Rosen Pub. Group, 1999)
Provides information on job opportunities in the field of graphic arts, discussing educational requirements, specific types of jobs, and the impact of computers on the way graphic artists work.
Includes bibliographical references (p. 125-127) and index.
Keywords: Graphic arts -- Vocational guidance -- Juvenile literature; Graphic arts -- Vocational guidance; Vocational guidance